Consensus statement on normothermic regional perfusion in donation after circulatory death: Report from the European Society for Organ Transplantation's Transplant Learning Journey. (18th November 2021) - Jochmans, Ina; Hessheimer, Amelia J.; Neyrinck, Arne P.; Paredes, David; Bellini, Maria Irene; Dark, John H.; Kimenai, Hendrikus J. A. N.; Pengel, Liset H. M.; Watson, Christopher J. E.; ,
Summary: Normothermic regional perfusion (NRP) in donation after circulatory death (DCD) is a safe alternative to in situ cooling and rapid procurement. An increasing number of countries and centres are performing NRP, a technically and logistically challenging procedure. This consensus document provides evidence‐based recommendations on the use of NRP in uncontrolled and controlled DCDs. It also offers minimal ethical, logistical and technical requirements that form the foundation of a safe and effective NRP programme. The present article is based on evidence and opinions formulated by a panel of European experts of Workstream 04 of the Transplantation Learning Journey project, which is part of the European Society for Organ Transplantation. Abstract : Normothermic regional perfusion (NRP) in donation after circulatory death (DCD) is a safe alternative to in situ cooling and rapid procurement. This consensus document provides evidence‐based recommendations on the use of NRP in uncontrolled and controlled DCDs. It also offers minimal ethical, logistical and technical requirements that form the foundation of a safe and effective NRP programme. The present article is based on evidence and opinions formulated by a panel of European experts of Workstream 04 of the Transplantation Learning Journey project, which is part of the European Society for Organ Transplantation.